The Effect of Web Quests on Academic Achievement in Handball for Female Sophomore Students of Physical Education and Sport Sciences College/ University of Baghdad - Hamdan, Abdullah; Al-Sodany, Ahmed Khamees (Journal of Physical Education, 2022)
The research aimed at designing electronic program for web quest accompanied with an educational program for scientific handball classes to identify its effect on academic achievement in handball. The researchers used the experimental method on (60) sophomore female students of physical education and sport Sciences College/ university of Baghdad for the academic year 2021 – 2022. The subjects were divided into three equal groups to collected the data that was treated using SPSS to conclude that web quest educational program is suitable for teaching handball for sophomore students as well as it enables students to improve their cognitive level in handball. The researchers recommended applying web quest in handball for second year college of physical education and sport sciences students.